Crystallization, melt inclusion, and redox history of a Martian meteorite; olivine-phyric shergottite Larkman Nunatak 06319 - Peslier, A. H.; Hnatyshin, D.; Herd, Christopher D. K.; Walton, Erin L.; Brandon, Alan D.; Lapen, T. J.; Shafer, J. T. (My University, 2010)
The Larkman Nunatak (LAR) 06319 olivine-phyric shergottite is composed of zoned megacrysts of olivine (Fo (sub 76-55) from core to rim), pyroxene (from core to rim En (sub 70) Fs (sub 25) Wo (sub 5) , En (sub 50) Fs (sub 25) Wo (sub 25) , and En (sub 45) Fs (sub 45) Wo (sub 10) ), and Cr-rich spinel in a matrix of maskelynite (An (sub 52) Ab (sub 45) ), pyroxene (En (sub 30-40) Fs (sub 40-55) Wo (sub 10-25) ,), olivine (Fo (sub 50) ), Fe-Ti oxides, sulfides, phosphates, Si-rich glass, and baddeleyite. LAR 06319 experienced equilibration shock pressures of 30-35 GPa based on the presence of localized shock melts, mechanical deformation of olivine and pyroxene, and complete transformation of plagioclase to maskelynite with no relict birefringence. The various phases and textures of this picritic basalt can be explained by closed system differentiation of a shergottitic melt. Recalculated parent melt compositions obtained from melt inclusions located in the core of the olivine megacrysts (Fo (sub >72) ) resemble those of other shergottite parent melts and whole-rock compositions, albeit with a lower Ca content. These compositions were used in the MELTS software to reproduce the crystallization sequence. Four types of spinel and two types of ilmenite reflect changes in oxygen fugacity during igneous differentiation. Detailed oxybarometry using olivine-pyroxene-spinel and ilmenite-titanomagnetite assemblages indicates initial crystallization of the megacrysts at 2 log units below the Fayalite-Magnetite-Quartz buffer (FMQ-2), followed by crystallization of the groundmass over a range of FMQ-1 to FMQ+0.3. Variation is nearly continuous throughout the differentiation sequence. LAR 06319 is the first member of the enriched shergottite subgroup whose bulk composition, and that of melt inclusions in its most primitive olivines, approximates that of the parental melt. The study of this picritic basalt indicates that oxidation of more than two log units of FMQ can occur during magmatic fractional crystallization and ascent. Some part of the wide range of oxygen fugacities recorded in shergottites may consequently be due to this process. The relatively reduced conditions at the beginning of the crystallization sequence of LAR 06319 may imply that the enriched shergottite mantle reservoir is slightly more reduced than previously thought. As a result, the total range of Martian mantle oxygen fugacities is probably limited to FMQ-4 to -2. This narrow range could have been generated during the slow crystallization of a magma ocean, a process favored to explain the origin of shergottite mantle reservoirs.
Keywords: achondrites; cosmochemistry; crystallization; electron probe data; geochemistry